EFFECTS OF LOCAL ANASTESI USING LIDOCAIN OINTMENT ON WHITE RATS (RATTUS NORVEGICUS) - Aprilia putri efendy; Deyke K. Baderan; Arif Hidayat Arbie (Journal of Health, Technology and Science (JHTS), 2022)
This study aims to determine the effectiveness of drug administration, namely lidocaine ointment on male and female white rats (Rattus Norvegicus) as well as to see the comparison of water samples given to experimental animals and lidocaine ointment given to experimental animals and see the effects that occur when lidocaine ointment is given to the experimental animals. experimental animal. The method used is a laboratory experimental method using 20 experimental male and female white rats which were divided into 2 groups, namely the male and female rats. cold, hot sensation of pain sensation and touch sensation in the observation period. The results showed that lidocaine ointment smeared on the left arm on white rats had a smaller number of sensation responses than any given stimulus. This shows that lidocaine ointment has the effectiveness of local anesthesia while water does not have a local anesthetic effect because the nerves in the arm are still able to respond well to the stimuli given.